The Mediating Role of Knowledge Sharing on the Relationship between Social Networking, Reputation, Social Interaction and Work Efficiency in PT. Taspen (Persero) - Achiriah, Rizka; Herjanwinardi, Catur; Hidayat, Yanuar Faqih; Damayanti, Nur (APMBA (Asia Pacific Management and Business Application), 2022)
This study examines the mediating effect of knowledge sharing on work efficiency, which influenced by social networking, reputation, and social interactions. A survey questionnaire conducted among 320 respondents. The result of hypothesis testing was conducted by Smart PLS 3.0. The result shows that social networking and reputation were directly and significantly related to work efficiency. Meanwhile, social interactions were not directly significant related to work efficiency. The knowledge sharing was found to be directly and significantly related to work efficiency. Knowledge sharing mediates the relationship between social networking, reputation, social interactions, and work efficiency. The results of this study could foster organizations to be able to support the knowledge sharing process among employees in a conducive manner to improve work efficiency. Organizations can also encourage the effectiveness of knowledge sharing by giving awards to employees who have participated as contributors. This is intended to reduce the tendency to be reluctant to share knowledge among employees. Further research can be explored more deeply factor that influence work efficiency such as communication, time management, and work culture.